Patient’s safety during simultaneous bilateral total knee arthroplasty - Zazirnyi, I M; Strokan, A M; Savych, V V; Levytskyi, Ye A (Pain medicine, 2022)
Abstract. As the utilization of total knee arthroplasty increases and the population ages, the number of patients who require surgical treatment of both knees is rising. These procedures may be conducted simultaneously or sequentially; the simultaneous bilateral approach is increasingly considered the preferred option because it permits a symmetric recovery while avoiding risks associated with an additional operation, anesthetic, hospitalization, and recovery period while reducing the costs associated with sequential procedures. Despite these advantages, concerns have been raised regarding increased risks for deep vein thrombosis, pulmonary embolism, cardiac complications, and mortality. Results reported in the literature with regards to the relative safety of these procedures have been conflicting; however, it is agreed upon that careful patient selection is essential for reducing risk associated with simultaneous bilateral total knee arthroplasty. A set of guidelines have been established which may be used to help guide the management of patients with bilateral degenerative joint disease seeking knee replacement surgery. Key words: bilateral total knee arthroplasty, simultaneous bilateral total knee arthroplasty, staged bilateral total knee arthroplasty, total knee arthroplasty.